Traumatic Penetrating Neck Injury with Right Common Carotid Artery Dissection and Stenosis Effectively Managed with Stenting: A Case Report and Review of the Literature - Seidu A. Richard; Chang Wei Zhang; Cong Wu; Wang Ting; Xie Xiaodong (Case Reports in Vascular Medicine)
Introduction. Penetrating neck injuries (PNI) are common and associated with arterial and other neuronal injuries. Although many authors have written on penetrating and blunt carotid artery injuries as a result of PNI or traumatic neck injuries, no one has reported a case or case series on PNI that resulted in blunt carotid dissection and stenosis. Case Presentation. We present a case of 40-year-old building and construction male worker who slipped and fell on an iron rod that resulted in penetrating wound on the right side of the anterior neck a week prior to presenting at our facility. He pulled out the iron rod immediately. Computer tomography angiography (CTA) done revealed C2-C4 transverse process fractures on the right side and a fracture at the right lamina of C3 and right common carotid artery dissection with stenosis. He was successfully treated with stenting via endovascular approach. Conclusions. We adopt the view that patient should never pull out objects that result in PNI because of complex neurovascular architecture of the neck. The mortality rate of our patient will have doubled if the iron rode penetrated the common carotid artery. The gold standard treatment option for carotid artery dissection and stenosis is endovascular approaches.